Diversity and abundance of hymenopteran species in mixed-use agricultural landscape of Pusat Penyelidikan Pertanian Tun Razak, Pahang, Malaysia - Muhammad Haziq Aiman Aubaidellah; Nur Amalina Mohd Izam; Siti Khairiyah Mohd Hatta; Dzulhelmi Muhammad Nasir; Siti Asmah Muslim; Nur Athirah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Hymenoptera are ubiquitous insects crucial for ecosystem balance, fulfilling diverse ecological roles as pollinators, parasitoids, and predators, serving as valuable bioindicators of environmental health. While Hymenoptera communities in homogeneous agricultural landscapes have been extensively studied, research on heterogeneous mixed-use systems in Malaysia remains limited. Thus, the objectives of this study are to produce a checklist of Hymenoptera and to compare their diversity and composition across four land cover types namely oil palm plantations (OP), fruits orchards (FO), forest remnants (FR), and urban areas (UA) within the Pusat Penyelidikan Pertanian Tun Razak (PPPTR). A total of 3,455 individuals of Hymenoptera from 22 families and 148 morphospecies were identified during the study period. This study also found a significant difference in the abundance (df = 3, P<0.05) and richness (df= 3, P<0.05) of Hymenopteran species across different land covers of PPPTR, Pahang. Fruit orchards (H’ index = 5.624) and oil palm plantations (H’ index = 5.352) support a higher diversity of Hymenoptera in comparison to forest remnant (H’ index = 4.398) and urban areas (H’ index = 5.107), though in a smaller number of individuals. Forest remnant and urban areas hold different hymenopteran communities altogether, with 35% similarity from the orchard and oil palm plantation. This preliminary study shows that mixing different land cover patches within an agricultural landscape may promote different diversity and abundance of Hymenoptera. Cropped habitat apparently holds substantial value in providing resources for the Hymenoptera, through good management practices are needed to increase its population size. Additional study is needed to characterize the environmental variations between each cover type for a better understanding of the influence of mixed-use agricultural landscapes on Hymenoptera communities.